ALGAL DIVERSITY AND PHYSICO-CHEMICAL PARAMETERS IN HADHINARU LAKE, MYSORE, KARNATAKA STATE, INDIA - S. H. BASAVARAJAPPA,; N. S. RAJU,; S. P. HOSMANI,; S. R. NIRANJANA, (The Bioscan, 2010)
Phytoplankton diversity in Hadhinaru lake of Mysore has been discussed. Five diversity indices have been derived using the PASTA software programme. They include, Shannon and Wiener index, Berger and Parker dominance index, Bellan and Santini index, Simpson index and Pielous evenness index. A total of 29 algal species were recorded during December 2008 to November 2009.Chlorococcales was recorded in higher numbers, while Cyanophyceae and Desmidaceae were low in number. The evenness and dominance of species in the lake was not well marked. The lake becomes heavily polluted during March, May, October and November. The Bray and Curtis Similarity index reveals that Euglena oxyuris, Cymbella cymbelliformis, Pinnularia gibba, Actinastrum hantzschii, Tetradron lobatum, Euglena elastica and Lepocinclis ovum have the highest similarity and can co-exist in a common cluster. Diversity indices serve as an important tool in understanding the distribution of phytoplankton in lakes.